Pembelajaran Matematika dengan Memanfaatkan Formulator Tarsia - Ani Afifah (Didaktik Matematika, 2017)
Mathematics is often regarded as a difficult subject in school, consequently many students are less interested in learning it. The use of technology can be an alternative to create an interesting and effective of instructional Media. One of the application programs that teachers can choose is Tarsia Formulators. This formulator is a program designed for math teachers to create puzzles, dominoes, and other forms of activity. This paper discusses examples of the application of puzzles created from tarsia formulators in mathematics learning. Learning activities begin by introducing the form of puzzles to be assembled by the students. The teacher gives an explanation of the rules that apply in this lesson. Teacher guides need to be done to make it easier for students who have difficulty. Furthermore, the teacher displays the correct form of the puzzle in comparison to the student's work and provides an explanation of the answer to the problem presented. The tarsia formulators makes it easy for teachers to create effective and varieties instructional media, so students do not feel bored in classroom learning activities.